Biodiesel Production from Crude Karanja Oil using Heterogenous Catalyst from Seashells - Saleh, A.A.; Dewi, Harreh; Sinin, Hamdan (2020)
The virus that causes COVID-19 spreads primarily through droplets generated when an infected person coughs, sneezes, or speaks. Someone can also be infected by touching a contaminated surface, then touching their eyes, nose, or mouth before washing their hands. People are advised to clean hands regularly and thoroughly, and avoid touching eyes, mouth, and nose to keep safe from the virus. Cleaning has never been a greater concern than it is today since the COVID-19 pandemic has spread throughout the world. However, methanol, ethanol, and chlorine-based are often used in cleaning and disinfectingproductstokillthevirusonsurfaces.Thesechemicalscalledvolatileorganic compounds (VOCs) which are found in commonly used conventional cleaning products. Theexcessiveusageoftheseproductswillcauseindoorairpollutionandothernumerous health implications which are very harmful to the building occupants and especially for the clean workers and the people with health conditions. Therefore, it is important to implement a green cleaning programme to reduce the issue of environmental health impact. This paper aims to discuss the benefits green cleaning and how to maintain cleanliness in a green way and without damaginghealth. This paper is anticipated to be significantly beneficial and can be further used as a piece of information for facilities management and thepeople.